Neutral Copper Gas Resistivity Measurements by Means of an Exploding Wire in Air - Bilbao, Luis Ernesto (2017)
In this work, we present experimentally obtained limits for the values of the neutral copper gas electrical resistivity as a function of the temperature. When a current of about ≈ 103 A or larger flows through a metallic wire in a microsecond or shorter time, the wire performs a phase change from solid to plasma, through intermediate states of metallic liquid and vapor. If the wire is surrounded by a non-conductive dense medium that inhibits the circulation of current outside the wire (e.g., air at room temperature and standard pressure, as in our experiments), the electric current stops when part of the metallic wire becomes gas. This process is known as dark pause, and it has a duration that depends on the experiment parameters. By means of a suitable choice of parameters, we achieved a duration of the dark pause of ≈1 µs, which allowed us to determine the limits of the electrical resistivity of the metallic gas. The range of measured values starts from the resistivity of liquid copper at boiling temperature, and goes up to ≈0.01 (±20%) Ohm·m at the maximum measured temperature.